Comparative analysis of different hybrid energy system for sustainable power supply: A case study. Issue 1 (March 2020) - Bista, Aayush; Khadka, Nasib; Shrestha, Ashish; Bista, Diwakar
Abstract: Hybrid Power System (HPS) is an energy system with combination of different regenerative energy sources like Solar, Wind, Geo-Thermal, Biomass and several others to achieve energy sustainability. This paper investigates the feasibility of grid connected and stand-alone hybrid energy system to meet electric load requirement of a community or organization, by utilizing the available resources. Potentiality of different energy sources like solar, wind, bio-gas, etc. along with currently used energy sources is studied thoroughly by taking a case study of Kathmandu University central campus, located at Dhulikhel, Nepal. Technical and economic analysis of on-grid and off-grid hybrid system is performed to get optimum model that supply continuous energy to the end user. Furthermore, the possibility of net metering with national utility has been analysed. The main objective of this study is to identify the suitable energy mixed model, that provide the sustainable energy supply to the university, and recommend the possible energy generators to be added for fulfilling the continuously increasing load demand. The load profile of several years of the University is taken into consideration for forecasting the power demand. The findings of the research show that system when adopted to hybrid system can meet up to 55% of the load by renewable resources. Maximum renewable fraction is found to be 0.603 and maximum renewable penetration of 812%.